THE EFFECTIVENESS OF THE STARSTREAK MISSILE DEFENSE SYSTEM PREPARATION STRATEGY IN SUPPORTING THE INDONESIAN ARMY'S MAIN TASKS (STUDY AT THE 14TH AIR DEFENSE BATTALION/PWY): EFEKTIVITAS STRATEGI PENYIAPAN ALUTSISTARUDAL STARSTREAK DALAM MENDUKUNG TUGAS POKOK TNI AD (STUDI DI YONARHANUD 14/PWY) - Pujo Andriana; Guntur Eko Saputro; Edy Saptono (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This research aims to identify and analyze the readiness condition of the Starstreak Missile Alutsista (Main Weaponry System) at Yonarhanud 14/PWY (Air Defense Artillery Battalion 14/PWY), formulate strategies to improve its readiness, and develop a framework to measure the effectiveness of the implementation of these strategies. A qualitative research method with a case study approach was used. The research results indicate that the current readiness condition of the Starstreak Missile Alutsista is not yet optimal. Several influencing factors include: 1) Unfulfilled number of Alutsista; 2) Limited number and competence of technicians; 3) Limited facilities and infrastructure; 4) Inadequate budget support; and 5) Dependence on external parties. The proposed strategies include improving personnel, facilities and infrastructure, budget support, self-maintenance capabilities, and coordination.